1983
DOI: 10.1111/j.1524-4725.1983.tb00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytologically Malignant Squamous‐Cell Carcinoma Arising in a Verrucous Carcinoma of the Penis

Abstract: A case of verrucous carcinoma with a focus of cytologically malignant squamous-cell carcinoma is presented. This usually occurs following radiation therapy of the verrucous carcinoma, but may rarely occur de novo, as in this case. The potential usefulness of fine-needle aspiration in detecting focal anaplasia in verrucous carcinoma is discussed. This technique may be especially useful if the lesion is to be destroyed cryosurgically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Development of a squamous carcinoma in a pre‐existing verrucous carcinoma has been reported following radiotherapy. 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of a squamous carcinoma in a pre‐existing verrucous carcinoma has been reported following radiotherapy. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Development of a squamous carcinoma in a pre-existing verrucous carcinoma has been reported following radiotherapy. 28 Our findings provide supportive evidence that PKMB has malignant potential. Beljaards et al 1 have suggested that an alternative name, micaceous and verrucous malignant balanitis, should replace PKMB.…”
Section: Discussionmentioning
confidence: 99%
“…Verrucous carcinoma exhibits characteristic cell kinetics that are more akin to those of normal mucosa than they are to conventional squamous cell carcinoma. 100, [102][103][104][105] In particular, DNA synthesis (S-phase) is confined to the basal cell layer, along with the more conventionally detected mitotic activity. The lack of S-phase cells above the basal cell layer is quite unlike the findings in conventional squamous cell carcinomas.…”
Section: Human Papillomavirus-associatedmentioning
confidence: 99%
“…The lack of S-phase cells above the basal cell layer is quite unlike the findings in conventional squamous cell carcinomas. 100,103,104 Verrucous carcinomas may be diploid or aneuploid. 104,106 In the Choi et al 107 analysis of microsatellite markers in head and neck squamous cell carcinomas, verrucous carcinomas showed similar losses when compared with conventional, well-differentiated squamous cell carcinomas.…”
Section: Human Papillomavirus-associatedmentioning
confidence: 99%
“…[5][6][7][8][9] FNAC has detected focal anaplasia in verrucous carcinoma. 11 In the only reported series, 11 patients underwent FNAC of the penis. FNAC diagnosed five metastatic lesions, one benign lesion, and three lesions that were primary ulcerative SCC.…”
Section: Casementioning
confidence: 99%